(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Mental health disorders among adolescents and young adults represent a growing global public health challenge. Mobile health (mHealth) applications have emerged as accessible and scalable tools for providing psychosocial support and self-help interventions. This narrative review synthesizes findings from recent systematic reviews and meta-analyses (2019–2025) on the effectiveness, engagement, safety, and methodological quality of mental health apps targeting depression, anxiety, and related conditions in youth. Evidence suggests small-to-moderate effects of app-based interventions in controlled trials, particularly when incorporating cognitive-behavioral therapy (CBT) and mindfulness-based strategies. However, engagement and retention remain major barriers, and evidence on long-term outcomes and adverse events is limited. Methodological shortcomings, such as small sample sizes and short follow-up periods, constrain generalizability. Future research should prioritize high-quality randomized trials, sustainable engagement strategies tailored to youth populations, and integration of digital interventions into clinical and educational systems with stronger regulatory oversight on content validation and data security.